Improving Serious Games to Tackle Childhood Obesity - Belghali, Maroua; Statsenko, Yauhen; Al-Za’abi, Abdulsalam (Frontiers in Psychology, 2021)
Childhood obesity has become a global public health issue. Today, there are opportunities to promote health through technological devices such as serious games. Despite the major advancement of this field of research, the use of serious games as a validated intervention in clinical practice requires further clarifications on some methodological aspects. In this perspective article, we report the pros and cons of existing serious games. Besides, we attempt to propose a new methodology of design of a serious game that could help to cope with childhood obesity. The proposed idea consists of a serious game in virtual reality based on enjoyment, movement, education, and executive functioning training. Longitudinal studies and solid research protocol would certainly ensure consistency and aid interpretation.